1986
DOI: 10.1038/319640a0
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of cDNA encoding the murine IgG1 induction factor by a novel strategy using SP6 promoter

Abstract: Complementary DNA encoding the IgG1 induction factor, the first lymphokine directed to B lymphocytes, from a murine T-cell line has been cloned using a new strategy. The putative primary amino-acid sequence was deduced from the nucleotide sequence determined. The lymphokine synthesized by the direction of this cloned cDNA has many other functions, such as production of B-cell growth factor-1 and induction of Ia on B cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
175
0
3

Year Published

1986
1986
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 460 publications
(186 citation statements)
references
References 41 publications
8
175
0
3
Order By: Relevance
“…Subsequent to biochemical purification (27) and molecular cloning (28,29), it was reported that II.,-4 and IgG1 enhancing factor, also called B cell differentiation factor-,/ (BCDF-~,), arc the same lymphokine (30). IL-4 was later shown to act also on T cells as well as on other cell types including monocytes, endothelial cells, and fibroblasts (13,31).…”
Section: Vol 40 No 6 1996mentioning
confidence: 99%
“…Subsequent to biochemical purification (27) and molecular cloning (28,29), it was reported that II.,-4 and IgG1 enhancing factor, also called B cell differentiation factor-,/ (BCDF-~,), arc the same lymphokine (30). IL-4 was later shown to act also on T cells as well as on other cell types including monocytes, endothelial cells, and fibroblasts (13,31).…”
Section: Vol 40 No 6 1996mentioning
confidence: 99%
“…Recently, evidence has been accumulated to show that the growth of B cells and their differentiation into antibody producing cells require several soluble factors. Three factors regulating the B cell response have been reported in the human ; interleukin-4 (IL-4) for the early activation of resting B cells (Noma et al 1986; Yokota et al 1986), IL-5 for the growth of activated B cells , and IL-6 for the final differentiation of B cells into antibody producing cells (Hirano et al 1985(Hirano et al , 1986. It has been reported that cardiac myxoma patients showed autoimmune symptoms, hypergammaglobulinemia, and autoantibody production which could be mediated by a large amount of IL-6 released from myxoma .…”
mentioning
confidence: 99%
“…No responses to the transmitters were observed under these conditions in oocytes injected with aequorin alone This approach offers several advantages over assay techniques which are currently being used to clone Ca 2 +-mobilizing receptors [ 15,17,18]. The present method is rapid and convenient; no radioisotopes are required and no electrophysiological expertise or equipment is necessary.…”
Section: Methodsmentioning
confidence: 91%